Pengaruh Kompensasi dan Motivasi terhadap Produktivitas Kerja: Studi Kasus Karyawan Food and Beverage di Tangerang Selatan - Mohammad Zein Saleh; Muhammad Farhan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research explores the influence of compensation and motivation on employee productivity in the Food & Beverage industry in South Tangerang. Employing a quantitative method with a sample of 100 respondents, regression analysis results indicate that both compensation and motivation significantly contribute positively to productivity. Compensation contributes by 0.146 units, while motivation contributes by 0.119 units to the increase in productivity. Although the model explains only around 20.5% of the variation in productivity, the study provides significant insights. It is concluded that fair compensation policies and enhanced motivation can boost employee performance. Despite unexplained variations, these findings offer a foundation for companies to improve human resource management policies.